Fostering Entrepreneurial Competencies in Higher Education: Trends, Challenges, Legal Issues and Impacts on Student Success - Zarrina Rakhimova; Bakhromjon Topildiev; Shavkat Nazarov; Mokhigul Kadirova; Nozimakhon Sobirova; Manzura Rustamova; Khamida Nusratova (Qubahan Academic Journal, 2025)
In an age where innovation and adaptability define economic success, the development of entrepreneurial competencies in higher education has become both a priority and a necessity. While prior research has extensively documented the effectiveness of experiential learning in fostering entrepreneurial mindsets, few studies bridge the expectations of such training with its real-world institutional challenges. This study contributes to that dialogue by examining how structured entrepreneurship education at ISFT Institute affects students' entrepreneurial self-efficacy, business creation rates, and employability. Drawing from a sample of 162 students and combining qualitative and quantitative data, the findings indicate that hands-on learning significantly outperforms traditional theoretical instruction in nurturing entrepreneurial intent. Notably, access to mentorship and industry networks amplifies these effects. However, despite these gains, the study underscores persistent challenges, including limited funding, fragmented policy implementation, and faculty resistance, which create a misalignment between policy ambition and operational reality. The absence of a significant research gap in the literature emphasizes the urgency for translating well-documented strategies into practice. This paper argues that a holistic, interdisciplinary approach—paired with regulatory and institutional reforms is critical to achieving the full potential of entrepreneurship education in higher education institutions.